ANALISIS SWITCHING INTENTION KONSUMEN TERHADAP PENGALAMAN BELANJA ONLINE DARI SOCIAL COMMERCE KE E-COMMERCE MENGGUNAKAN FAKTOR PUSH, PULL DAN MOORING - Muhammad Daffa Wahanandra, (2022)
The tradition of shopping online has become a habit for everyone, whether through social commerce or e-commerce. However, currently shopping on social commerce has several risks, such as especially for security because the social commerce platform cannot cover the end-to-end online transaction process on the platform. E-commerce on the other hand, can still be relied on to ensure security and ease of transactions. These characteristics may encourage users to switch to E-commerce from the initial social commerce. This study has the aim of understanding a complete understanding of the factors that influence users to migrate with push, pull and mooring (PPM) factors. This study uses a quantitative approach with data collection using online questionnaires filled out by consumers who have shopped online through social commerce and E-commerce. The data analysis process uses PLS-SEM with SmartPLS. The results of this study indicate that the push factor has a positive influence in encouraging consumers to leave social commerce, while the pull factor consists of security and ease of use issues that positively affect consumers in using E-commerce. While the mooring factor consists of habits that affect the intention to switch. Keywords: social commerce, E-commerce, Switching Intention, PPM (Push, Pull and Mooring)